Clash Between Spiritualism and Materialism in Kamla Markandaya’s Possession - A Critical Study - Vanza Ketan Punjabhai (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
Kamla Markandaya (1924-2004) is a notable Indian-English author. She possesses a diverse subject matter, a profound awareness of India's socio-political developments, a mastery of the English language, and a style of narration and description that provokes thinking. She has reflected the country's ways of thinking, customs, and way of life, as well as its scenery and people. In her works, the East-West setting is shown as confrontation or conflict. It is a recurring and ubiquitous motif in the majority of her writings. The aim of present paper is to examine a collision of values between the East and the West or between spiritualism and materialism in her novel, Possession.In this novel, there is a clash between Indian spiritualism and western materialism, the former winning the latter.